Antipsychotic use and Risk of Venous Thromboembolism: A Meta-Analysis. (February 2021) - Di, Xuan; Chen, Muyi; Shen, Su; Cui, Xiangli
Highlights: Antipsychotic drugs increase the risk of Venous thromboembolism(VTE) and pulmonary embolism(PE). Young people are at a higher risk of VTE when they take antipsychotics than elderly people. The risk of VTE and PE is associated with second-generation AP drugs (SGAs), Low-potency first-generation AP drugs (FGAs) and antipsychotic combination treatment. Abstract: Objective: This study aimed to evaluate the association between antipsychotic drugs (APs) and the risk of venous thromboembolism (VTE). Methods: We searched Pubmed, Embase, and the Cochrane Library from inception to August 15, 2019 for case-control studies and cohort studies that explored the association between APs and VTE. Two researchers independently screened the literature, extracted the data and evaluated the bias risk included in the study. Meta-analysis was carried out by using STATA 13.0. Results: 1, 468 studies were identified through database search, and 22 studies were finally included (14 case-control studies and 8 cohort studies). Overall, the APs usage was associated with increased risk of VTE and pulmonary embolism (PE) with no publication bias. Both the first-generation APs (FGAs) and second-generation APs (SGAs) can increased the risk of VTE. The low-potency FGAs lead to a higher risk of VTE than high-potency FGAs. The risk of PE and VTE in younger patients was about 3-fold higher compared with elderly. Conclusion: This review demonstrates that APs usage can increase the risk of VTE. Young people are at a higher risk of VTE than elderly when taking APs.